Monetary Policy and Balanced Public Administration under the Contemporary Economic Context - Punjakhan, Piyasun (MCU Haripunchai Review, 2026)
This article examines the relationship between monetary policy and balanced public administration in the contemporary economy, integrating perspectives from public administration and macroeconomics. It conceptualizes monetary policy as a state policy instrument encompassing interest rate management, money supply control, and policy communication, which is closely linked to public administration through institutional coordination, legitimacy, and good governance. The study highlights three key dimensions. First, monetary policy functions as a strategic public instrument for macroeconomic regulation and the enhancement of economic security. Second, monetary policy is intrinsically related to balanced public administration through the integration of economic, social, and governance dimensions in policy management. Third, the article proposes future directions for balanced public administration that emphasize flexible governance, systems learning, inter-agency coordination, and public participation. The article advances a dynamic public administration framework that views monetary policy not merely as an economic tool, but as a core governance mechanism for sustaining equilibrium between economic growth and long-term sustainability.